Amphiphilic Pentablock Copolymers Prepared from Pluronic and ε-Caprolactone by Enzymatic Ring Opening Polymerization - Ahmed Abd El-Fattah; Elizabeth Grillo Fernandes; Federica Chiellini; Emo Chiellini (International Journal of Molecular Sciences, 2022)
Amphiphilic copolymers are appealing materials because of their interesting architecture and tunable properties. In view of their application in the biomedical field, the preparation of these materials should avoid the use of toxic compounds as catalysts. Therefore, enzymatic catalysis is a suitable alternative to common synthetic routes. Pentablock copolymers (CUC) were synthesized with high yields by ring-opening polymerization of ε-caprolactone (ε-CL) initiated by Pluronic (EPE) and catalyzed by Candida antarctica lipase B enzyme. The variables to study the structure–property relationship were EPEs’ molecular weight and molar ratios between ε-CL monomer and EPE macro-initiator (M/In). The obtained copolymers were chemically characterized, the molecular weight determined, and morphologies evaluated. The results suggest an interaction between the reaction time and M/In variables. There was a correlation between the differential scanning calorimetry data with those of X-ray diffraction (WAXD). The length of the central block of CUC copolymers may have an important role in the crystal formation. WAXD analyses indicated that a micro-phase separation takes place in all the prepared copolymers. Preliminary cytotoxicity experiments on the extracts of the polymer confirmed that these materials are nontoxic.